ANTIHYPERTENSIVE EFFECT OF RUTIN: PHARMACOLOGICAL AND COMPUTATIONAL APPROACH: PHARMACOLOGICAL AND COMPUTATIONAL APPROACH - GANGA RAJU M; PREM PRASAD GOUD; SUVARCHALA REDDY NVL (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Phenolic compounds, such as flavonoids, have aroused great scientific interest due to their diverse pharmacological activities. Several studies suggested that flavonoids act as antihypertensive by inhibiting angiotensin-converting enzyme (ACE). In the present study, rutin, which is a citrus flavonoid, was evaluated for its antihypertensive activity using in vivo and in vitro models. Rutin was screened for in vitro assay procedures such as diphenylpicrylhydrazyl and nitroblue tetrazolium (NBT) for its antioxidant activity. Methods: Its antihypertensive effect was investigated in Nω-Nitro-l-arginine methyl ester hydrochloride-induced hypertensive rats, and various parameters such as blood pressure and heart rate were measured; in vitro ACE inhibitory activity was carried out against ACE, aiming at a better understanding of the interaction of this flavonoid with the enzyme. To understand its binding affinity with the angiotensin-converting enzyme, molecular docking studies were carried out using ligand fit of Maestro 9.1 (Schrodinger Software Inc.). An in silico study of rutin was performed for the prediction of Absorption, distribution, metabolism and elimination (ADME) by utilizing a web-based program (www.swissadme.ch). This software computes physicochemical descriptors as well as predicts pharmacokinetic properties and drug-like nature of one or multiple small molecules (blood–brain barrier, cytochromes P450, and P-glycoproteins). Results: Rutin at different dose levels of 200 and 400 mg/kg was tested, and the results have shown its antihypertensive, hypotensive, and negative chronotropic effects. Its antihypertensive activity might be mediated through angiotensin-converting enzyme inhibition (half maximal inhibitory concentration=66.01 μg/mL). In vitro studies also revealed the antioxidant activity of rutin, thus playing a major role in reducing oxidative stress associated with hypertension. The rutin showed optimum binding affinity with a molecular target (angiotensin-converting-enzyme) with the binding energy of −9.0 kcal/mol as compared to the standard (−6.3 kcal/mol). These results indicated that rutin is one of the potential ligands to treat hypertension. ADME results revealed the three violations of rutin (such as molecular mass, hydrogen donor, and acceptors) of five, and the standard captopril has got zero violations which clearly indicated the probability for its higher oral bioavailability. Conclusion: From the above, it is concluded that rutin possesses antioxidant and antihypertensive activities.